The Influence of Financial Literacy, Lifestyle, and Pay Later Use on Consumptive Behavior - Pamungkas, Wihandaru Sotya; Putri, Shinta Irfanny (Indonesian Journal Publisher, 2024)
This research aims to obtain empirical evidence and analyze the impact of financial literacy (FL), lifestyle (LS), and use of pay later (UPL) on student consumptive behavior (CB). This research involved students from the Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta as the subjects. Samples were taken using the purposive sampling method, namely students who used pay later, and the accidental sampling method, namely students who were easy to find. The total sample collected was 135 people. Hypothesis testing was carried out using the structural equation modeling (SEM) method via AMOS software. The results showed that improvements in FLT, LST, and UPL contributed to the increase in SCB. These findings indicate that students who understand financial services should be able to control themselves, so they do not behave impulsively. However, they behave consumptively because they are encouraged to be accepted by their group members and have an extravagant lifestyle. This condition can be achieved because there is ease of payment using pay later.